Advice & dissent the struggle to shape the federal judiciary - Binder, Sarah A. (Brookings Institution Press, 2009)
"Explores the state of the federal judicial selection system. Reconstructs the history and contemporary practice of advice and consent, identifying political, institutional causes of conflict over judicial selection and consequences of such battles. Advocates pragmatic reforms of the institutions of judicial selection that harness incentives of presidents and senators together"--Provided by publisher.